THE ROLE OF CORRECTIONAL GUARDIANS IN SUPPORTING SOCIAL REINTEGRATION THROUGH INMATE EMPOWERMENT IN CLASS IIA BANJARMASIN PRISON - Nabawi, Muhammad Rizki; Tando, Cahyoko Edi; Aulia, Qisthina (Universitas Nusa Cendana, 2025)
This study aims to explore the role of correctional guardians in supporting social reintegration through prisoner empowerment at Banjarmasin Class IIA Correctional Facility. The method used is a case study with a qualitative approach, involving interviews, observation, and documentation. The main informants include the head of the prison, the head of the work section, and correctional guardians. The results show that correctional guardians have an important role in guiding and motivating prisoners to participate in empowerment programs, such as skills training and personality development. However, the implementation of this program still faces various obstacles, including a lack of human resources, limited facilities, and problems with inmate motivation. Specialized training for correctional guardians and increased collaboration with external parties are recommended to strengthen the effectiveness of empowerment programs and support the social reintegration of prisoners. Keywords: Correctional Guardians; Social Reintegration; Prisoner Empowerment